WAYS TO INCREASE THE SOCIAL ACTIVITY OF STUDENTS BY SHAPING EDUCATIONAL ACTIVITIES IN THE EDUCATIONAL PROCESS (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The article examines ways to increase students' social activity by shaping educational activities within the educational process. Today, school education represents the longest stage of human education and is a crucial factor for both individual success and the long-term development of a country. The article discusses the main tasks of forming positive and stable motivation among students towards educational activities, as well as modern educational strategies based on a personal and competency-based approach. The research develops a model for forming positive and stable motivation for educational activities, which is based on principles such as scientific and systematic approach, subjectivity, activity and independence, development and activity, practical orientation, collectivism, and reflection. This model aims to enhance students' socialization and motivation for success through organized group activities. Results indicate that students' positive and stable motivation is linked to intellectual self-awareness, skills in group educational activities, and readiness to self-assess their abilities.